Genomic Investigation of Virulence Potential in Shiga Toxin Escherichia coli (STEC) Strains From a Semi-Hard Raw Milk Cheese - Cortimiglia, Claudia; Borney, Maria Francesca; Bassi, Daniela; Cocconcelli, Pier Sandro (Frontiers in Microbiology, 2021)
Shiga-toxin producing Escherichia coli (STEC) represents a significant cause of foodborne disease. In the last years, an increasing number of STEC infections associated with the consumption of raw and pasteurized milk cheese have been reported, contributing to raise the public awareness. The aim of this study is to evaluate the main genomic features of seven STEC strains isolated from a semi-hard raw milk cheese, focusing on their pathogenic potential. The analysis of seventy-five cheese samples collected during the period between April 2019 and January 2020 led to the isolation of seven strains from four stx-positive enrichment. The genome investigation evidenced the persistence of two serotypes, O174:H2 and O116:H48. All strains carried at least a stx gene and were negative for eae gene. The virulence gene pattern was homogeneous among the serogroup/ST and included adherence factors (lpfA, iha, ompT, papC,saa, sab, hra, hes), enterohaemolysin (ehxA), serum resistance (iss, tra), cytotoxin-encoding genes like epeA, espP and the pathogenicity island LAA-PAI typically found in LEE negative STEC. Genome plasticity indicators, namely prophagic sequences carrying stx genes and plasmid replicons, were detected, leading to the possibility to share virulence determinants with other strains. Overall, our work adds new knowledge on STEC monitoring in raw milk dairy products, underlining the fundamental role of WGS for typing these unknown isolates. Since, up to now, some details about STEC pathogenesis mechanism lacked, the continuous monitoring in order to protect human health and increase knowledge about STEC genetic features becomes essential.